Miejsce Policji w życiu społecznym - Wierzbicki, Marcin (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2017)
Police fully recognizably plays an important role in life of every citizen. Without an adequate level of security of social life and economic would be much more difficult.This article makes an attempt to present the role of the police in a modern society. Indicate the source and essence of the social demand for police services and the impact of social expectations on the manner in which the ranking police tasks. Determination of the ratio between the use of repression and the performance of the role of guardian is a difficult and complex task. In order to ensure their security, every citizen is obliged to waive part of their liberties andfreedom. The huge influence of the mass media to create awareness of social causes Police is also involved in the creation of channels of information favorable in relation institutioncitizen.